A century in books : Princeton University Press, 1905-2005. (Princeton University Press, 2005)
It all began atop a drugstore in Princeton, New Jersey, in November 1905. From its modest beginnings, Princeton University Press was to become one of the world's most important scholarly publishers, embracing a wealth of disciplines that have enriched our cultural, academic, and scientific landscape.Both as a tribute to our authors and to celebrate our centenary, Princeton University Press here presents A Century in Books. This beautifully designed volume highlights 100 of the nearly 8,000 books we have published. Necessarily winnowed from a much larger list, these books best typify what has been most lasting, most defining, and most distinctive about our publishing history--from Einstein's The Meaning of Relativity (1922) to the numerous mathematical and other works that marked the Press's watershed decade of the 1940s, including von Neumann and Morgenstern's Theory of Games and Economic Behavior; from milestones of literary criticism by Erich Auerbach and Northop Frye to George Kennan's Pulitzer Prize-winning book on Soviet-American relations; from Milton Friedman and Anna Jacobson Schwartz's A Monetary History of the United States, 1867-1960 to more recent landmarks such as L. Luca Cavalli-Sforza, Paolo Menozzi, and Alberto Piazza's The History and Geography of Human Genes and Robert Shiller's Irrational Exuberance.In addition to succinct descriptions of the 100 titles and a short introduction on the history of the Press, the book features five essays by prominent scholars and writers: Michael Wood discusses the impact on Princeton University Press of intellectuals who fled Nazi Germany and authored many influential books. Anthony Grafton recounts our rich publishing tradition in history, politics, and culture. Sylvia Nasar traces our evolution into a leading voice in economics publishing. Daniel Kevles reflects on Einstein, a figure of special importance to Princeton. And Lord Robert May writes on our long-standing tradition of publishing in mathematics and science.A Century in Books is more than a celebration of 100 years of publishing at Princeton University Press--it is a treasure trove of 100 years of books that have added to the richness of twentieth-century intellectual life.
Keywords: Princeton University Press -- History.; Princeton University Press; University presses -- New Jersey -- History.; New Jersey -- Imprints.; Presses universitaires -- New Jersey -- Histoire.; New Jersey -- Imprimés.; LANGUAGE ARTS & DISCIPLINES / Publishing; University presses; New Jersey; Ancient history.; Archival research.; Astronomer.; Author.; Book design.; Book series.; Burckhardt.; Capitalism.; Career.; Celestial mechanics.; Computation.; Econometrics.; Economist.; Editing.; Edition (book).; Editorial.; Empiricism.; English literature.; Episode.; Eranos.; Erudition.; Essay.; Facsimile.; From Caligari to Hitler.; Historicism.; Humanities.; Illustration.; Institution.; Intellectual history.; Interwar period.; Lecture.; Literature.; Mainframe computer.; Mathematician.; Mathematics.; Modern architecture.; Modern history.; Modernity.; Monarchies in Europe.; Monograph.; Narrative.; Novelist.; Number theory.; Of Education.; Old Testament.; Philology.; Philosopher.; Philosophy.; Physicist.; Poetry.; Political science.; Politics.; Printing.; Publication.; Publishing.; Renaissance art.; Renaissance.; Scientist.; Textbook.; The New York Review of Books.; The New York Times.; Theory.; Time series.; Time value of money.; Title page.; Tradition.; World War II.; Writing.; Bibliographies; History